Variabilidade espacial da umidade relativa do ar no interior de uma casa de vegetação em clima tropical - Voltan, Diego S. [UNESP]; Barbosa, Rogério Z. [UNESP]; Perea Martins, João E.M. [UNESP] (Revista Brasileira de Ciencias Agrarias, 2014)
Greenhouse with natural ventilation is widely used in tropical countries, and little knowledge is available about how this type of structure affects the spatial variability of agroclimatic variables. The aim of this study was to analyse the spatial variability of relative humidity inside a greenhouse with natural ventilation. The measurement of relative humidity was done at 114 points inside the greenhouse at 9, 12 and 16 hours and on heights of 0.3, 1.2 and 2.0 m. The acquired data were processed by the geostatistical software GS+ and maps were generated and displayed for each time and height using the Surfer 10.3.705 software. The results showed that there were variations in the spatial distribution of relative humidity inside the greenhouse.
Spatial variability of relative humidity inside tropical greenhouse
Keywords: Agroclimatology; Geostatistics; Glasshouse condition